The floor is Q-LavHA A study about Hafnarfjörður and the rising volcanic activity on the Reykjanes peninsula, Iceland - Derenius, Rebecca; Gao, Josie (2022)
The 2021 eruption in Fagradalsfjall might have activated a new era of volcanic activity on the Reykjanes peninsula. To study possible eruptions and its impact, one way of simulating lava flow using QGIS is through the plugin Q-LavHA. To validate the method, a reference flow from Fagradalsfjall was digitized and showed accuracy when simulating a new flow with parameters in Manhattan Length, lining up with the reference flow. Manhattan Length is a QLavHA parameter for simulating a lava flow line following the travel distance. This validates the method of the plugin enough to line up with the original flow from Fagradalsfjall. The same parameters for Fagradalsfjall were then used on a fissure south of Hafnarfjörður, to simulate a potential lava flow. However, it does have a different topography than Fagradalsfjall and could therefore mean a different outcome. The method after simulating a possible flow in Hafnarfjörður from the reference flow in Fagradalsfjall was to simulate a “worst-case scenario” using the plugin but changing and using FLOWGO as a parameter. This was simulated with a flow similar to water, to get a longer extent that reaches Hafnarfjörður to analyze how the town could be affected and the possible lava flow pathway. This was done on both Fagradalsfjall and Hafnarfjörður, to see how the plugin would use the new parameters in FLOWGO compared to each other. It did show a longer extent and that the topography has an important role in the simulated flow, as Hafnarfjörður is flat while Fagradalsfjall has a variety of heights. The worst-case scenario flow on Fagradalsfjall did not reach the nearest town Grindavík, according to Q-LavHA, while the worst-case scenario for Hafnarfjörður reached the town. The next step was to change topography using the previous flow and add it to the Digital Elevation Model (DEM), then simulate a new flow and a worst-case scenario flow on top of that near Hafnarfjörður. This was also done for Fagradalsfjall but with the new DEM with changed topography already added from the ...